Thrombolytic Therapy Within 3 to 6 Hours After Onset of Ischemic Stroke - Peter A. Ringleb; Peter D. Schellinger; Corinna Schranz; Werner Hacke (2002)
Background — The use of recombinant tissue plasminogen activator (rtPA) within 3 hours after onset of an ischemic stroke is an established therapy. Because the use of intravenous rtPA beyond a time window of 3 hours after stroke onset is still a matter of debate, we sought to review the evidence for the use of thrombolytic therapy in a time window up to 6 hours after onset of symptoms of ischemic stroke. Summary of Review — The meta-analyses of the major trials (National Institute of Neurological Disorders and Stroke rtPA Stroke Study, European Cooperative Acute Stroke Study [ECASS] I, ECASS II) showed a benefit of thrombolytic therapy with intravenous rtPA even within 6 hours after onset of symptoms of ischemic stroke. The rate of intracerebral hemorrhage was slightly increased in the 6-hour time window compared with the 3-hour time window (odds ratio, 3.23 versus 2.68), but this was without statistical significance because of wide confidence intervals. A positive effect of 37% relative odds reduction with the use of a dichotomization of ≤2 versus ≥3 on the modified Rankin Scale remains for rtPA treatment within 6 hours. However, the Alteplase Thrombolysis for Acute Noninterventional Therapy in Ischemic Stroke (ATLANTIS) Study, in which a 3- to 5-hour time window was used, failed to show a benefit of rtPA. Still, when the results of ATLANTIS are included into meta-analyses such as the Cochrane Library, the positive effect of rtPA treatment in the 6-hour time window remains, with a “number needed to treat” value of 11. Treating patients only within a 3- to 6-hour time window would lead to a number needed to treat value of 25. Conclusions — Consequently, from our point of view it appears unjustified to limit thrombolytic therapy to 3 hours. Because of lack of approvals for 3 to 6 hours, thrombolytic therapy within this time window should be done only as part of an institutional protocol after extensive information is obtained from the patient and the patient’s relatives. Better methods for patient selection are required; in particular, newer MRI techniques, such as diffusion- and perfusion-weighted imaging, can play a key role. The aim is to qualify and individualize the time window according to the findings in each patient’s imaging results rather than to use a strictly time-defined therapeutic window.